Caracterização molecular de Avipoxvirus isolados de casos clínicos de bouba aviária em aves domésticas - Talita Gomes da Silva Batista (2018)
The poxviruses form a complex family of viruses, among the oldest known, capable of infecting several classes of animals. Avipoxviruses (APV) are members of genus Avipoxvirus and, as all poxviruses, characterized as large enveloped viruses with a double - stranded DNA. APV cause avian pox, a nodular disease of a proliferative nature, in more than 200 species of commercial and wild birds, causing economic and environmental losses. This study describes the molecular characterization of ten isolates of APV diagnosed in natural clinical cases birds attended at the avian diseases laboratory of the Federal University of Minas Gerais. Four strains of chickens, two of turkeys, two of pigeons and two of canaries were submitted to PCR and sequencing analyses. The phylogenetic reconstruction, from the sequencing of the gene encoding the 4b protein (fwp167), showed that these strains clustered in clade A and clade B. We emphasize the importance of studies for the characterization of APV isolates, especially in species with great capacity for agent dissemination, such as the pigeons analyzed in the study.